Managerial Leadership and Public Service Quality: Service Behavior as a Mediator, Evidence from Ethiopia - Legas, Abreham; Abagissa, Jemal (Jejaring Administrasi Publik, 2025)
With rising public expectations for accountability and citizen-oriented services, improving public service quality (PSQ) remains a critical challenge for government organizations. Addressing this challenge requires a deeper understanding of how internal leadership practices translate into external service outcomes. This study investigates the behavioral pathways through which managerial leadership (ML) impacts PSQ, focusing on employee service behavior (SB) as a mediating mechanism. Anchored in behavioral leadership theory and the leader–member exchange (LMX) framework, the research employs a quantitative design with survey data from 768 public service employees and service users in Ethiopia. Using structural equation modeling (SEM), the study finds that the integration of task-focused managerial practices and relationship-oriented leadership behaviors substantially enhances service quality. Leaders who set clear roles and goals, monitor performance, and simultaneously inspire, empower, and support employees strengthen perceptions of reliability, responsiveness, and trustworthiness in public institutions. The findings advance the argument that an integrative leadership approach, blending the administrative precision of management with the motivational and relational strengths of leadership, constitutes a powerful lever for promoting PSQ. This study not only contributes to the growing body of knowledge on the leadership–service quality nexus but also provides actionable insights for public managers seeking to meet growing citizen demands through hybrid leadership strategies. Keywords: managerial leadership, public service quality, service behavior, behavioral theory of leadership, leader-member exchange theory, service-oriented leadership